A Pancreatic Inflammatory Myofibroblastic Tumor with Spontaneous Remission: A Case Report with a Literature Review - Hiroyuki Matsubayashi; Katsuhiko Uesaka; Keiko Sasaki; Seitaro Shimada; Kazunori Takada; Hirotoshi Ishiwatari; Hiroyuki Ono (Diagnostics, 2019)
The inflammatory myofibroblastic tumor (IMT) is a rare tumor that can develop in any systemic organ. Its features are generally benign, but it often resembles malignancies and is treated surgically. Our patient was an 82-year-old female complaining of abdominal discomfort. Computed tomography demonstrated a 5 cm, ill-enhanced mass at the pancreas head. Upper gastrointestinal endoscopy revealed a duodenal submucosal tumor with apical erosion. Endoscopic ultrasonography (EUS) demonstrated a heterogeneous, low-echoic pancreas mass without clear margins. Fine-needle aspiration biopsy (FNAB) demonstrated spindle myofibroblastic tissues with lymphoplasmacyte and eosinophil infiltration, confirming an IMT diagnosis. Surprisingly, the tumor spontaneously regressed in one month without medication. Histological diagnosis using EUS-FNAB is essential for the rare pancreatic solid tumor like IMT.